1996
DOI: 10.1128/jb.178.15.4530-4539.1996
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent growth kinetics of Escherichia coli ML 30 in glucose-limited continuous culture

Abstract: Knowledge concerning the influence of environmental factors such as temperature, pH, salinity, etc., on microbial growth is of crucial practical importance in the control of bioprocesses, for the safe handling of food (1, 2, 12, 50, 51), in wastewater treatment (7), and in bioremediation (2). In addition, in taxonomy, cardinal temperatures for growth are key characteristics of microbial strains (37).In recent years, several models for predicting the growth rate of microorganisms as a function of either tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 49 publications
4
37
0
Order By: Relevance
“…In earlier work on the growth of E. coli in glucoselimited chemostat culture at 37 1C (Senn et al, 1994), we found that s ¼ f(D) three kinetic models fitted the data with similar quality (Monod, Shehata and Marr, Westerhoff). Extending this work to suboptimal and superoptimal temperatures (17, 28 and 40 1C), we experimentally observed a clear indication for the existence of a finite glucose concentration at zero growth rate, and when extending the classical Monod model with an s min , the obtained kinetic data could be fitted well and statistically better than with any other model of similar complexity (Kovárová et al, 1996). Hence, the original (1) and the extended Monod model (2) were the obvious model of choice to be applied to our competition experiments.…”
Section: Modellingmentioning
confidence: 86%
See 3 more Smart Citations
“…In earlier work on the growth of E. coli in glucoselimited chemostat culture at 37 1C (Senn et al, 1994), we found that s ¼ f(D) three kinetic models fitted the data with similar quality (Monod, Shehata and Marr, Westerhoff). Extending this work to suboptimal and superoptimal temperatures (17, 28 and 40 1C), we experimentally observed a clear indication for the existence of a finite glucose concentration at zero growth rate, and when extending the classical Monod model with an s min , the obtained kinetic data could be fitted well and statistically better than with any other model of similar complexity (Kovárová et al, 1996). Hence, the original (1) and the extended Monod model (2) were the obvious model of choice to be applied to our competition experiments.…”
Section: Modellingmentioning
confidence: 86%
“…The most important one is the very low residual substrate concentrations under which this competition takes place; they are usually in the range of a few mg per litre, that is, below detection limit. Therefore, in contrast to earlier studies at higher growth rates (Senn et al, 1994;Kovárová et al, 1996;Lendenmann et al, 2000), K s can usually not be determined by measuring the residual concentration of the growth controlling substrate. Another aspect is that slow-growing cells (for example, from a low D in continuous culture) are usually not able to immediately increase the rate of growth when transferred to substrate excess conditions.…”
Section: Growth Kineticsmentioning
confidence: 93%
See 2 more Smart Citations
“…Growth rates in most experiments were saturating functions of dissolved nitrogen concentration, S (μ = μ max [S/K s + S]), permitting calculation of the Monod kinetic parameters K s (half-saturation constant) and μ max (maximum growth rate). In 2 instances, an extended form of the Monod model (μ = μ max [(S -S min )/(K s + S -S min ]) was employed because negative growth was observed below a finite nutrient concentration (S min ; Kovarova et al 1996). Monod constants were estimated by 2 methods; indirectly by Eadee-Hofstee linear transformation and directly by iterative non-linear curve fitting (Marquardt-Levenberg method: SPSS SigmaPlot version 8.0).…”
Section: Methodsmentioning
confidence: 99%